When tourism becomes an ecological threat: Do institutional quality and ICT make a difference in Ghana? - Musah, Mohammed; Onifade, Stephen Taiwo; Prempeh, Kwadwo Boateng; Ankrah, Isaac; Nkyi, Joseph Akwasi (Elsevier, 2026)
Achieving ecological sustainability remains a pressing global challenge as anthropogenic activities increasingly strain planetary boundaries. Why does tourism (TR) expansion continue to degrade ecological carrying capacity in developing economies, and how can institutional quality and ICT moderate this relationship? This study examines the tourism-ecological sustainability nexus in Ghana using the load capacity factor (LCF) as a comprehensive environmental measure, employing Kernel Regularised Least Squares (KRLS) as the primary estimator and Quantile-on-Quantile Regression (QQR) as a robustness check on data spanning 1996-2024. The results reveal that TR consistently deteriorates LCF across all quantiles, with stronger ecological damage at lower development levels. Institutional quality exhibits threshold dynamics: initially worsening, then eventually improving environmental outcomes beyond critical governance thresholds. ICT demonstrates uniformly negative effects, reflecting the energy-intensive demands of digital infrastructure, while financial development displays extreme heterogeneity, transitioning from negative to potentially positive effects at higher levels of development. These findings underscore the urgency of integrating institutional reforms, green digital infrastructure, and environmentally aligned financial regulations into Ghana's sustainable tourism frameworks, with broader policy implications for SDG-compliant strategies across Sub-Saharan Africa.
Keywords: Environmental sustainability; Tourism sector; ICT & institutional quality; Load capacity factor; Quantile-on-quantile regression; Ghana; fi=Taloustiede|en=Economics|